Study of the relationship between functional clinical vulnerability and depression in elderly people attending a social group - Sousa, Natieles Castelo Branco de; Soares, Mariana de Castro; Costa, Leiane Mota; Everton, Amanda Cunha Bandeira; Soares, Ana Karina Arruda Abdala; Junior, José Jonas Pinheiro Soares; Carvalho, Sarah Tarcisia Rebelo Ferreira de; Soares, Karla Virgínia Bezerra de Castro (Seven Editora, 2024)
Introduction: Aging is a natural process of life, but it also causes difficulties in locomotion, relationships, and understanding, both through speech and cognitive understanding. These difficulties can generate vulnerability, dependence and psychological illnesses, such as depression. Objective: To analyze the possible relationship between clinical functional vulnerability and depression in elderly people attending a social group. Materials and method: Analytical cross-sectional study carried out in a senior living center in São Luís, MA, with a sample of 30 elderly people who met the inclusion criteria. Sociodemographic, economic and health questionnaires prepared by the researchers were applied to understand the sample profile. To assess functional vulnerability, the Functional Clinical Vulnerability Index (IVCF-20) was used and to assess depression, we chose the GDS Scale- 15, both validated for application with the Brazilian population. In the analysis of correlations, Pearson (r) coefficient was applied, considering a significance level of 5%. Results: Sample consisting of 30 elderly people, 77% of whom were women, with 54% aged between 75 and 80 years. Of these, 83% presented moderate and high risk of vulnerability, with 30% already showing depressive symptoms between moderate and severe. The correlation between vulnerability and depression was positive, indicating (rs)=0.5339 and (p)=0.0028. Conclusion: the relationship between the risks of clinical-functional vulnerability and depressive symptoms in the elderly is evident, with emphasis on women, highlighting the importance of early screening of psychological fragility and its association with the dimensions of functionality, essential measures to propose care interventions capable of guaranteeing autonomy, independence and quality of life for this population. DOI:https://doi.org/10.56238/sevened2024.001-018